Flexural behavior and water absorption of asymmetrical sandwich composites from natural fibers and cork agglomerate core - Hoto, R. (2014)
This work addresses an experimental investigation concerning flexural and water absorption behavior of a novel low-cost green composite asymmetric sandwich. For specimen manufacturing, an agglomerate cork panel and natural fiber reinforcements, namely basalt and flax fiber were used. A bio-based epoxy resin was used as matrix and the specimens were manufactured using vacuum assisted hand lay-up. For some specimens the core material was altered allowing resin infiltration between the granules. Results show that both, the core type and specimens׳ stance influence the flexural behavior. More importantly, all specimens showed a very good energy absorption behavior during bending tests. The water absorption of the specimens was significantly reduced by the infiltration of resin inside the core material. These attractive performances reveal that the green composites based sandwich proposed in this work can be a good alternative to traditional ones.